Unencumbered and still unequal? Work hour - Health tipping points and gender inequality among older, employed Australian couples - Tinh Doan; Christine LaBond; Cathy Banwell; Perri Timmins; Peter Butterworth; Lyndall Strazdins (Elsevier, 2022)
Could working into older age offer women an opportunity to 'catch up' their careers and redress their financial disadvantage in retirement? This is a period of relative 'unencumbrance' from childrearing, potentially freeing women's time for more paid work. Here, we examine whether women aged 50 to 70 are able to increase their workhours, and what happens to their mental health, vitality and wealth. We used a representative household-based panel of employed older Australians (the HILDA survey). The longitudinal bootstrapped 3SLS estimation technique adjusted for reciprocal relationships between wages, workhours, and health, modelled in the context of domestic work time. We found that, relative to their same-aged male counterparts, older women spent 10 h more each week on domestic work, and 9 h less on work that earned income. When women sought to add more paid hours on top of their unpaid hours, their mental health and vitality were impaired. Men were typically able to maintain their workhours and health advantage by spending fewer hours each week on domestic work. Unable to work longer without trading-off their health, and paid less per hour if they did so, our analysis questions whether working into older age offers women a road out of inequality and disadvantage.